Improving the interview skills of college students using behavioral skills training. Issue 3 (23rd March 2017) - Stocco, Corey S.; Thompson, Rachel H.; Hart, John M.; Soriano, Heidi L.
Abstract : Obtaining a job as a college graduate is partly dependent on interview performance. We used a multiple baseline design across skills to evaluate the effects of behavioral skills training with self‐evaluation for five college students. Training effects were evaluated using simulated interviews as baseline and posttraining assessments. All participants acquired targeted skills, but we observed some individual differences. Participants were satisfied with training outcomes and rated the procedures as acceptable. Furthermore, ratings from university staff who provide interview training indicated that training improved performance across several skills for the majority of participants.